A Decade of Empirical Research on Research Integrity: What Have We (Not) Looked At?. (October 2019) - Aubert Bonn, Noémie; Pinxten, Wim
Research on research integrity has become a field of its own; yet, a comprehensive overview the field is still missing. We systematically searched SCOPUS, Web of Science, and PubMed for relevant articles published between 2005 and 2015. We extracted the topic, methodology, focus, and citations from each articles. From the 986 articles included, only 342 report empirical data. Empirical papers predominantly targeted researchers and students. Although empirical articles questioning causes for misconduct mostly blamed research systems (e.g., pressure, competition) for detrimental research practices, articles proposing approaches to foster integrity focused on researchers' awareness and compliance rather than on system changes. Involving nonresearchers and reconnecting what is known to what is proposed may help research on research integrity move forward.